IFSB Standards Adoption and Its Impact on Islamic Banking Practic-es: Evidence from Pakistan - Ali, Azam; Zulkhibri , Muhamed; Kishwar, Kishwar (Journal of King Abdulaziz University: Islamic Economics, 2022)
The adoption of the Islamic Financial Services Board (IFSB) criteria for Islamic banks is more challenging for a bigger number of supervisory and regulatory authorities than for conventional banks. This paper investigated the IFSB-15 standard; revised capital adequacy standard for institutions offering Islamic financial services [excluding islamic insurance (takāful) institutions and islamic collective investment schemes], by evaluating the possibility of its adoption within a dual banking system and introduced an analysis of the effects of Islamic banks in Pakistan. The study found that in practise, investment account holders are treated as conventional depositors that are capital-guaranteed rather than basing that allocation on the basis of profit and loss sharing (PLS) in accordance to Sharīʿah norms and stipulations. This treatment forced Islamic banking institutions to take a market-perspective approach to profit distribution. This makes them ensure a steady profit pay-out (paying a competitive rate of return by accepting displaced commercial risk). The paper therefore suggested that the implementation of technical standards has to be accompanied with institutional growth, like that involved in the Islamic banking structure and institutional capacity in accordace to the substance of Sharīʿah norms and stipulations rather than the form.